Knowledge and Attitude Toward Breastfeeding among Female Medical Students - Reema Salih; Salem Fathallah; Haneen Mustafa; Esra Nouri; Tasneem Elnaje (AlQalam Journal of Medical and Applied Sciences, 2025)
Breastfeed is an optimal food for the newborn and is efficient in ensuring child survival and health. This study was conducted to assess the extent of knowledge of the fourth- and fifth-year female students of the Faculty of Human Medicine, University of Derna about breastfeeding and its benefit for the mother and child. A questionnaire based- cross-sectional investigation was carried out on 150 students from the fourth and fifth female medical students of the faculty of human medicine at the University of Derna. The research was conducted in a period from 1stof April to 1st of November 2024.Most participants in a study received breastfeeding information (98.9%) from lectures, doctors, and friends or relatives. (57.1%) agreed that benefits last only while breastfeeding, while formula-fed babies have a higher risk of being overweight (75.3). Breastfeeding is considered healthier (89.6 %), but it is also considered more convenient and cheaper (83.8%). Breast milk is considered ideal, easier to digest (90.3 %), and cheaper than bottle feeding. Most participants support breastfeeding’s health benefits and convenience (79.2), while expressing mixed views on public breastfeeding and formula feeding. Breastfed babies are believed to have better immunity (86.4), promote better weight gain, and should be the first feeding for newborns (90.9). However, some participants feel neglected if breastfeeding is done in public. Undergraduate medical students have positive breastfeeding attitudes but need specific training for successful breastfeeding management and teaching to become excellent physicians. الرضاعة الطبيعية هي الغذاء الأمثل لحديثي الولادة وهي فعالة ضمان بقاء الطفل وصحته. أجريت هذه الدراسة لتقييم مدى معرفة طالبات الفرقة الرابعة والخامسة بكلية الطب البشري جامعة درنة عن الرضاعة الطبيعية وفائدتها للأم والطفل. تم إجراء استبيان مقطعي على 150 طالبة من طالبات الطب الرابع والخامس بكلية الطب البشري بجامعة درنة. تم إجراء البحث في الفترة من 1 أبريل إلى 1 نوفمبر 2024. تلقى معظم المشاركين في الدراسة معلومات عن الرضاعة الطبيعية (98.9%). من المحاضرات والأطباء والأصدقاء أو الأقارب. (57.1%) وافقوا على أن الفوائد تستمر فقط أثناء الرضاعة الطبيعية، في حين أن الأطفال الذين يتغذون على الحليب الاصطناعي يكونون أكثر عرضة لخطر زيادة الوزن (75.3). تعتبر الرضاعة الطبيعية أكثر صحة (89.6%)، ولكنها تعتبر أيضاً أكثر ملاءمة وأرخص (83.8%). يعتبر حليب الثدي مثالياً، وأسهل هضماً (90.3%)، وأرخص من الرضاعة بالزجاجة. يدعم معظم المشاركين الفوائد الصحية للرضاعة الطبيعية وملاءمتها (79.2)، بينما يعبرون عن آراء متباينة حول الرضاعة الطبيعية العامة والتغذية الصناعية. يُعتقد أن الأطفال الذين يرضعون رضاعة طبيعية يتمتعون بمناعة أفضل (86.4)، ويعززون زيادة الوزن بشكل أفضل، ويجب أن يكونوا أول تغذية لحديثي الولادة (90.9). ومع ذلك، يشعر بعض المشاركين بالإهمال إذا تمت الرضاعة الطبيعية في الأماكن العامة. يتمتع طلاب الطب في المرحلة الجامعية الأولى بمواقف إيجابية بشأن الرضاعة الطبيعية ولكنهم يحتاجون إلى تدريب محدد لإدارة الرضاعة الطبيعية وتدريسها بنجاح ليصبحوا أطباء ممتازين